2019
DOI: 10.1002/zoo.21471
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in the long‐term viability of North American zoo populations

Abstract: Recent concerns about the viability of zoo populations have motivated studies on the historic and current status of animal populations in North American and European zoos.However, these evaluations may not accurately reflect the populations' long-term viability in the decades to come. Here, we assessed the projected future status of North American zoo populations by conducting standardized population viability analyses (PVAs) for 137 cooperative breeding programs. We summarized PVA results to describe patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…When evaluating program status against the ark paradigm, analyses demonstrated that most of the world zoos’ managed breeding programs fell short of these sustainability measures (Lees & Wilcken, ; Leus et al, ; Long, Dorsey and Boyle, ). On the one hand, this led to increased efforts and new initiatives to improve population sustainability (e.g., AZA Task Force on the Sustainability of Zoo‐based Collections (Dorsey, Luke, and Boyle, ); PVA analysis of AZA's animal programs (Che‐Castaldo et al, ; Johnson, Clausen and Faust, ); the establishment of the World Association of Zoos and Aquarium (WAZA) Global Species Management Plans in 2007 (Gusset, )). Perhaps more importantly, it also caused a growing realization that a “one size fits all” approach is no longer the appropriate model (e.g., Baker et al, ; de Man, Leus and Holst, ).…”
Section: The Need For Integrated Conservation Planningmentioning
confidence: 99%
“…When evaluating program status against the ark paradigm, analyses demonstrated that most of the world zoos’ managed breeding programs fell short of these sustainability measures (Lees & Wilcken, ; Leus et al, ; Long, Dorsey and Boyle, ). On the one hand, this led to increased efforts and new initiatives to improve population sustainability (e.g., AZA Task Force on the Sustainability of Zoo‐based Collections (Dorsey, Luke, and Boyle, ); PVA analysis of AZA's animal programs (Che‐Castaldo et al, ; Johnson, Clausen and Faust, ); the establishment of the World Association of Zoos and Aquarium (WAZA) Global Species Management Plans in 2007 (Gusset, )). Perhaps more importantly, it also caused a growing realization that a “one size fits all” approach is no longer the appropriate model (e.g., Baker et al, ; de Man, Leus and Holst, ).…”
Section: The Need For Integrated Conservation Planningmentioning
confidence: 99%
“…The development of PMCTrack in 2008 by the Lincoln Park Zoo has enabled the AZA community to have a better understanding of how well zoos and aquariums are following the breeding and transfer recommendations issued by SSPs, which are the short‐term actions needed to guide populations towards long‐term viability (see Faust, Long, Perišin, & Simonis, this issue). More recent examples within AZA are population viability analyses (PVAs), which have been conducted for a number of species (see Che‐Castaldo et al, this issue), and an SSP Sustainability Database that was created to collate data for each SSP Program on population status, husbandry challenges, research needs, and sustainability action required (see Wilson, Dorsey, & Moore, this issue). All of these efforts aimed to clarify the sustainability challenges for individual managed programs so that individual facilities could take actions to align their resources with SSP Program needs to enhance the viability of their populations.…”
Section: Efforts To Address the Sustainability Crisismentioning
confidence: 99%
“…Finally, population viability analyses (PVAs) in some form or another have existed for over three decades now. Managers can apply lessons learned from PVA application to in‐situ populations to how they think about persistence of ex situ populations, specifically the roles of uncertainty, feedbacks, and population management goals in population persistence (see Lacy, this issue and Che‐Castaldo et al, this issue).…”
Section: Paths Forwardmentioning
confidence: 99%
“…Thus, zoos have long been estimating the equivalent of an MVP for managed populations. The recent effort by AZA to conduct PVAs on many species using ZooRisk (Che‐Castaldo et al, this issue) extends this approach, and the evolving PVA methods should increasingly be exploited to identify safe population sizes.…”
Section: Lessons About Threats To Wildlife Populationsmentioning
confidence: 99%
“…These challenges are not unique to ex situ populations, and PVA was developed to address these kinds of challenges in wildlife management. It has long been recognized that PVA has relevance also to ex situ population management (Foose, deBoer, Seal, & Lande, ), and the recent efforts by the AZA to assess the viability of its SSP populations (Che‐Castaldo et al, this issue) is a notable use of PVA. However, zoos globally have not yet fully embraced either the application of PVA methods for estimating likelihood of reaching goals or concepts from PVA for guiding how we think about population management.…”
Section: Introductionmentioning
confidence: 99%